2007
DOI: 10.3155/1047-3289.57.6.705
|View full text |Cite
|
Sign up to set email alerts
|

Variations in Speciated Emissions from Spark-Ignition and Compression-Ignition Motor Vehicles in California’s South Coast Air Basin

Abstract: The U.S. Department of Energy Gasoline/Diesel PM Split Study examined the sources of uncertainties in using an organic compound-based chemical mass balance receptor model to quantify the contributions of spark-ignition (SI) and compression-ignition (CI) engine exhaust to ambient fine particulate matter (PM2.5). This paper presents the chemical composition profiles of SI and CI engine exhaust from the vehicle-testing portion of the study. Chemical analysis of source samples consisted of gravimetric mass, elemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
78
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 110 publications
(94 citation statements)
references
References 1 publication
14
78
2
Order By: Relevance
“…In general, however, UFP exposures were greater in the English studies (Kaur et al, 2005b(Kaur et al, , 2006. As in this study, previous investigations have observed higher UFP levels in the morning relative to the evening hours, and this effect may be attributed to lower mixing heights and lower wind speeds during the morning hours (Kuhlbusch et al, 2001) as well as factors such as higher engine temperatures in the evening hours (Fujita et al, 2007). In addition, traffic densities may be higher during the morning hours (Cyrys et al, 2003;Young and Keeler, 2004;Aalto et al, 2005;Kaur et al, 2005aKaur et al, , b, 2006Jeong et al, 2006) as the evening rush hour is generally more spread out relative to the morning commute.…”
Section: Discussionsupporting
confidence: 45%
“…In general, however, UFP exposures were greater in the English studies (Kaur et al, 2005b(Kaur et al, , 2006. As in this study, previous investigations have observed higher UFP levels in the morning relative to the evening hours, and this effect may be attributed to lower mixing heights and lower wind speeds during the morning hours (Kuhlbusch et al, 2001) as well as factors such as higher engine temperatures in the evening hours (Fujita et al, 2007). In addition, traffic densities may be higher during the morning hours (Cyrys et al, 2003;Young and Keeler, 2004;Aalto et al, 2005;Kaur et al, 2005aKaur et al, , b, 2006Jeong et al, 2006) as the evening rush hour is generally more spread out relative to the morning commute.…”
Section: Discussionsupporting
confidence: 45%
“…Another possible explanation may be related to the cycle-average approach used in EMFAC versus the MOVES modal modeling approach. Vehicle emission tests have shown that a large fraction of the PM emissions from normal emitters are associated with hard acceleration events in the vehicle test cycle (Fujita et al, 2007). Measurements during the Kansas City Vehicle Emissions Characterization Study showed that the hard acceleration event that occurs between 840 and 880 sec of the unified driving cycle accounted for about 40% of the total hot running PM emission (Lindhjem et al, 2009) and that this fraction was similar for all model years newer than 1980.…”
Section: Discussionmentioning
confidence: 99%
“…The TIGF filters and XAD-4 extracts were analyzed separately by GC/MS, using a Varian CP-3800 GC equipped with a CP8400 autosampler and interfaced to a Varian 4000 ion trap for analysis of all semivolatile and condensed-phase organic compounds except hopanes and steranes, as described before (Fujita et al, 2007). Hopanes and steranes were analyzed using the Varian 1200 triple quadrupole gas chromatograph/mass spectrometer (GC/MS/MS) system with CP-8400 autosampler due to the higher sensitivity of this system.…”
Section: Sampling and Analysis Methodsmentioning
confidence: 99%
“…The main tracers of this factor are mostly associated to low molecular weight PAHs, namely, ACY, FLU, PHE and FLT, which could be associated mainly with diesel source emissions, since Wang et al, (2007) indicated the dominance of diesel combustion with the presence of three and four ring PAHs (such as FLT and PHE), as well as with oil combustion. Large emissions from diesel could be related also with the high concentrations of CRY which has been suggested as a diesel tracer ( Simcik et al 1999;Fujita et al 2007). The second factor was mostly associated with high molecular weight PAHs accounting 23.66% of the total variance.…”
Section: Source Identification Applying Statistical Analysismentioning
confidence: 98%